Accommodation stimulus and response determinations with autorefractors. (January 2017) - Atchison, David A.; Varnas, Saulius R.
Abstract: Purpose: To develop equations for accommodation stimulus and accommodation response with autorefractors when the accommodation stimulus is produced by combinations of object distances and lenses placed in front of eyes, and to give worked examples using these equations. Methods: Simple ray tracing was used to determine stimulus and response equations, taking into account the reference positions for targets, for refraction, and for autorefractor readings. Results: Several examples applying equations are provided. Features of these examples include evaluating approximate calculations that have been used previously, demonstrating which equations should be used in different circumstances, how to substitute numbers into equations, how to deal with discrepancies between subjective and objective refraction, and how to deal with astigmatism. Problems associated with measuring accommodation response by placing lenses in front of the eye are discussed. Conclusions: Accurate equations for accommodation stimulus and accommodation response for a range of accommodation stimuli in different setups have been developed.